The Puppeteer behind the scenes: Toward understanding ecosystem leadership mechanisms to grow IoT in South Africa. Issue 6 (11th May 2021) - Goshalia, Chetan; McDonogh, Jennifer; Mhlanga, Prins; Sewchurran, Kosheek
Abstract: The IoT digital revolution has opened opportunities to resolve complex, economic, environmental and social issues. Digitizing efforts involve participating in an ecosystem of innovators, providers, evolving customer needs and government policies. Companies entering this world report experiencing complexities with realizing value for stakeholders. This study presents a critical inquiry into the IoT world in South Africa. A grounded theory methodology is applied to provide an understanding of the important mechanisms at play affecting uptake of IoTs in the ecosystem. We use the insights to develop a model relevant for IoT players and urban planners to enhance benefit realization for the ecosystem as a whole. The study provides insight into a missing, "Puppeteering" role, that is required to organize ecosystem participants in their pursuit of value. A significant finding is that this role is best played by technology owners so that they can co‐create and generate jointly‐developed power to realize potential value for the entire ecosystem. The role needs to synergistically organize ecosystem participants to capture and distribute value to sustainably grow the ecosystem; and to engage in the development of required capabilities to sustain this. We argue that this "puppeteer effect" has potential to foster an inclusive, sustainable IoT strategy.